Strain accumulation in the New Madrid and Wabash Valley seismic zones from 14 years of continuous GPS observation. Issue 12 (5th December 2014) - Craig, Timothy J.; Calais, Eric
Abstract The mechanical behavior—and hence earthquake potential—of faults in continental interiors is an issue of critical importance for the resultant seismic hazard, but no consensus has yet been reached on this controversial topic. The debate has focused on the central and eastern United States, in particular, the New Madrid Seismic Zone, struck by four magnitude 7 or greater earthquakes in 1811–1812, and to a lesser extent the Wabash Valley Seismic Zone just to the north. A key aspect of this issue is the rate at which strain is currently accruing on those plate interior faults, a quantity that remains debated. Here we address this issue with an analysis of up to 14.6 years of continuous GPS data from a network of 200 sites in the central United States centered on the New Madrid and Wabash Valley seismic zones. We find that the high‐quality sites in these regions show motions that are consistently within the 95% confidence limit of zero deformation. These results place an upper bound on strain accrual on faults of 0.2 mm/yr and 0.6 mm/yr in the New Madrid and Wabash Valley Seismic Zones, respectively. For the New Madrid region, where a paleoseismic record is available for the past ∼5000 years, we argue that strain accrual—if any—does not permit the 500–900 year repeat time of paleo‐earthquakes observed in the Upper Mississippi Embayment. These results, together with increasing evidence for temporal clustering and spatial migration of earthquake sequences in continental interiors, indicate that either tectonic loading rates or fault properties vary with time in the New Madrid Seismic Zone and possibly plate wide.